PENGARUH PELAYANAN PRIMA TERHADAP CITRA SEKOLAH DI SMPN 50 - Khix Natu Saleha; Septi Repiani; Raudhotul Jannah; Nabilla Saputri; Irawati (Pendas : Jurnal Ilmiah Pendidikan Dasar, 2026)
This study aims to identify the influence of excellent service on school image at SMP Negeri 50 Pekanbaru. The author uses field research methodology in this study. Data collection was conducted through direct interviews, documentation studies, and direct observation at the research location. Data analysis employed a qualitative descriptive approach. The findings reveal that there are three main indicators of excellent service that affect school image, namely: the responsibility of administrative staff, speed and accuracy of administrative services, as well as the friendliness and service attitude of teachers and staff. These three indicators are implemented optimally by referring to the management functions of planning, organizing, actuating, and controlling in order to achieve a positive school image and enhance public trust toward SMP Negeri 50 Pekanbaru as a new school oriented toward national quality standards.